Taxonomy of Trigonocnera Reitter, with the description of a new species (Coleoptera, Tenebrionidae) - Ba, Yi-Bin; Ren, Guo-Dong (Zootaxa, 2009)
The genus Trigonocnera Reitter is reviewed. One new species is described under the name T. granulata sp. nov., and one subspecies in China, T. pseudopimelia pseudopimelia, is redescribed. A key to the species of the genus Trigonocnera is included.